REGULASI INFERIORITY MAHASISWA ASAL PEDALAMAN MELALUI BIMBINGAN KELOMPOK - Toni Elmansyah; Martin Martin (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2022)
Inferiority problems faced by students from the interior or the region are of concern to stakeholders in the field of guidance and counseling. Guidance and Counseling in College is an effort to help students to develop themselves personally, learningly, socially and career. The method used in this study is a descriptive method with its form of research action counseling guidance classes. Based on the results of research that has been conducted by researchers that group guidance services are effective against the regulation of student infiority from IKIP PGRI Pontianak. The conclusion in this study is 1) a picture of student infiority regulation of medium origin, 2). The implementation of effective group guidance services against inland student infiority regulations which include: planning, implementation, evaluation, observation and follow-up goes well in accordance with the plan that has been prepared or made. 3) Effective group guidance services against student infiority regulation from the interior this is proven to be a change in behavior.  The advice that can be given is; 1) Campus Counseling service units can create programs that suit the needs of students, 2). The results of this study can be used as a reference to obtain further guidance. 3). For study programs intensify services for students by increasing student activities.